Extract from the proceedings of the Senate of Pennsylvania, relative to the Kine-pock : Tuesday, January 30, 1810. Mr. Doty presented the memorial of Dr. James Smith, of the city of Baltimore, (enclosing an act of the legislature of Maryland,) which was read . - Smith, James, 1771-1841 ([publisher not identified], 1810)
Memorial to the General Assembly to authorize the provisions in a federal act which would allow free distribution of kine pock (cowpox) as a vaccine for smallpox. Included were an extract of the Pennsylvania proceedings and a report of Dr. James Smith to the Maryland General Assembly, both supportive of this vaccine.